Mobilising faith-based and lay leaders to address antenatal care outcomes in northern Ghana. Issue 5 (4th July 2017) - Hembling, John; McEwan, Elena; Ali, Mohammed; Passaniti, Anna; Aryee, Paul Armah; Saaka, Mahama
ABSTRACT: Despite the benefits of antenatal care, evidence from sub-Saharan Africa suggests that women often initiate these services after the first trimester of pregnancy and do not complete the recommended number of visits. This study examines the impact of mobilising faith-based and lay leaders to address the socio-cultural barriers to antenatal care uptake in northern Ghana in the context of a broader child survival project. A quasi-experimental design was used, and data were analysed using a difference-in-differences approach. The results presented in this article indicate the potential for faith-based and lay leaders to promote uptake of maternal and child health behaviours.